From parastatals to private trade: Lessons from Asian agriculture - Rashid, Shahidur; Gulati, Ashok; Cummings, Jr., Ralph (International Food Policy Research Institute, 2008)
Governments in Asia used grain price stabilization as a major policy instrument when they began to promote the Green Revolution in the 1960s. In the process, they created parastatal agencies, which were quasi-governmental in nature, to undertake public marketing activities in basic staples such as rice and wheat. These operations often meant providing a support price to farmers, procuring staples on government account, holding public stocks, and distributing these stocks through public distribution systems or open market operations to hold the price line for consumers. This led to a sizeable degree of government intervention in most of these countries' grain markets, which continues to a large extent today.